2013
DOI: 10.1016/j.mambio.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Invasion status of Asiatic red-bellied squirrels in Argentina

Abstract: The only known introduction of a squirrel species into South America is the case of the Asiatic red-bellied tree squirrel Callosciurus erythraeus that was introduced in the Pampas Region of Argentina in 1970. To inform management programmes, we analysed the current distribution, expansion rate, and abundance of the red-bellied squirrel in Argentina, and identified invasion pathways. Apart from the first and main focus of invasion, three other invasion foci have originated as a consequence of intentional releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
(46 reference statements)
2
22
0
Order By: Relevance
“…At present we cannot distinguish the invaded area that initiated at Arrecifes release site from the invaded area initiated at Capitán Sarmiento, therefore, we treat them as a single invasion focus resultant from two independent releases Date of release Cumulative number of releases Fig. 2 Cumulative number of successful (black dots) and failed (grey dots) release events of red-bellied squirrels recorded in Argentina per year, taking into account the four invasion foci previously described Lag in vector activity: Callosciurus translocations The spread rate described in these new invasion foci is comparable to the expansion rate observed throughout the first 30 years in the main invasion focus in Luján (0.53 km/year) that increased to 1.66 km/year between 20041.66 km/year between and 20091.66 km/year between (Guichón et al 2005Benitez et al 2013). The total invaded area in Argentina now exceeds 2100 km 2 though densities are quite variable.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…At present we cannot distinguish the invaded area that initiated at Arrecifes release site from the invaded area initiated at Capitán Sarmiento, therefore, we treat them as a single invasion focus resultant from two independent releases Date of release Cumulative number of releases Fig. 2 Cumulative number of successful (black dots) and failed (grey dots) release events of red-bellied squirrels recorded in Argentina per year, taking into account the four invasion foci previously described Lag in vector activity: Callosciurus translocations The spread rate described in these new invasion foci is comparable to the expansion rate observed throughout the first 30 years in the main invasion focus in Luján (0.53 km/year) that increased to 1.66 km/year between 20041.66 km/year between and 20091.66 km/year between (Guichón et al 2005Benitez et al 2013). The total invaded area in Argentina now exceeds 2100 km 2 though densities are quite variable.…”
Section: Discussionmentioning
confidence: 64%
“…3), but opposition to control actions is stronger in tourist and urban areas such as La Cumbrecita and Escobar (Fig. 3), even if the latter site has high conservation priority (Guichón and Doncaster 2008;Benitez et al 2013;Borgnia et al 2013). Prevention of new releases, which are illegal, should be a first national action that must prioritise areas of high conservation value and where native squirrels Sciurus aestuans and S. ignitus are present (Cassini and Guichón 2009;Borgnia et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other populations of C. erythraeus have been introduced in three Argentinian provinces due to its charismatic appearance . Interviews with local residents indicated that squirrels were subsequently translocated from the invasion focus in Luján to other locations within Argentina, where they were established as a consequence of intentional releases (Guichón et al 2005;Benitez et al 2013).…”
Section: Introductionmentioning
confidence: 99%